The Effect of the Digital Game Developed According to the RETAIN Model on Academic Achievement in the Subject of Household Wastes and Recycling - Yunus Emre Öner; Tohit Güneş (Uluslararası Türk Eğitim Bilimleri Dergisi)
People play games to have fun, and they are an important part of children's lives. People have used various materials to play games. With the development of technology, digital environments have also been used for games. The educational game method develops students' discovery, imagination, and high-level mental skills and provides permanent learning. Especially children spending time in digital environments has attracted the attention of educators. It is possible to transfer knowledge to students by using this time used by students in teaching environments or at home. In this study, the digital game developed by the researchers on household waste and recycling was evaluated according to the RETAIN model, and an achievement test was applied. The digital game was developed in 2D and RPG format using the Unity game development platform. It was determined that the digital game scored 46 points out of 63 points according to the RETAIN model weighting table. The research was conducted with 40 7th-grade students taking the course in the 2021-2022 academic year. A quasi-experimental design with a pre-test and post-test control group was used in the study. The achievement test developed by the researchers was used to collect data. When the post-test scores were examined, there was a significant difference in favor of the experimental group. The retention test was applied 5 weeks after the post-test and since there was no significant difference between the post-test and the retention test, it can be said that the effect of the application continues. Based on these results, it can be recommended to use this game developed for teaching the subject of household waste and recycling in teaching environments.